Effects of different soil and water conservation practices on soil physical and chemical properties in a non-terraced oil palm plantation - Moradi, Abolfath (2012)
Malaysia is the one of the two largest palm oil producers in the world and hence produces a huge amount of oil palm residues every year. Utilization of these residues as mulch and silt pitting are common practices used to conserve soil nutrients and water on non-terraced sloping lands and to improve soil physical and chemical properties linked to soil fertility. Therefore, a 3-year field experiment was set up to compare the effects of soil mulching with three different oil palm residues i.e. pruned oil palm fronds were considered as control, oil palm empty fruit bunches (EFB) and Eco-mat (ECO) which is a carpet like material made from EFB; and silt pitting on the soil physical and chemical properties and water conservation on a non-terraced oil palm plantation. EFB (37.5 t ha-1 y-1) and ECO sheets were applied annually on the soil surface as a single layer and pruned oil palm fronds (24 fronds per palm per year) were continually loaded in frond heaps. The silt pits were constructed by digging a trench along the hill contour, so that each one had a dimension of 4.0, 1.0, and 0.5 m in length, width, and depth, respectively. Soil samples from 0-0.15, 0.15-0.30 and 0.30-0.45 m depths were collected every three months for the first two years from each treatment plot and analyzed for organic C, total N, available P,exchangeable- K, Ca and Mg, pH, CEC, aggregate size distribution and aggregate stability. Soil bulk density, total porosity, water retention at different soil suctions,available water content and pore size distribution were also determined for 0-0.15 and 0.15-0.30 m soil depths. Soil water content up to 0.75 m depth was also measured daily. Frond No. 17 of the palms contributed to each plot was sampled every six months and analyzed for N, P, K, Ca and Mg. In the third year,decomposition and nutrient release patterns of the EFB, Eco-mat, pruned oil palm fronds and its components (leaflets and rachis) were also evaluated. Results showed that various oil palm residues had almost different patterns of decomposition and nutrient releases. EFB increased soil organic C, aggregate stability, mean weight diameter of soil aggregate, soil available water content, relative proportion of soil mesopores, pH, N, exchangeable K, Ca and Mg and improved oil palm leaf N, P, K,and Mg levels significantly. However, soil bulk density, total porosity, water retention at saturation and permanent wilting point, soil CEC and leaf Ca concentration were not affected by the soil conservation practices significantly. The effects of ECO and silt pitting on soil properties and oil palm nutrition were statistically the same and not different from control. Soil water content was also increased as a result of EFB mulching and silt pitting practices. However, silt pitting was not as effective as EFB in increasing water content in the topsoil. Therefore,utilization of the EFB as mulch is recommended for the purpose of increasing soil physical and chemical properties and water conservation in non-terraced oil palm plantations.